PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN DAYA SAING UMKM - Mariska Putri Pratiwi; Alice Erni Husein; Alfannisa Fajrin; Muhammad Haldy; Poppy Okta Fiana Putri (PUAN INDONESIA, 2026)
This community service program aimed to empower Micro, Small, and Medium Enterprises (MSMEs) through digital marketing training to enhance their competitiveness. Many MSME actors still face limitations in utilizing digital platforms for marketing purposes. The program involved 30 participants and was implemented through a series of practical training sessions covering social media marketing, e-commerce utilization, content creation, and basic search engine optimization (SEO). Evaluation was conducted using pre-test and post-test instruments as well as participant satisfaction surveys. The results showed an improvement in participants’ understanding of digital marketing concepts and practices, as well as a high level of satisfaction with the program. Participants reported increased confidence and readiness to adopt digital marketing strategies in their businesses. This program demonstrates that digital marketing training can be an effective empowerment approach to strengthen MSME capacity and competitiveness.